The effect of moderate to severe endometriosis on expression of growth differentiation factor‐9 mRNA in human granulosa cells under controlled ovarian hyperstimulation. (19th May 2015) - Kawabe, Sachiko; Yamashita, Yoshiki; Saito, Natsuho; Kokunai, Kana; Hayashi, Atsushi; Hayashi, Masami; Terai, Yoshito; Miyazaki, Kazunori; Ohmichi, Masahide
Abstract: Purpose: To investigate the effect of moderate to severe endometriosis on mRNA expression of growth differentiation factor‐9 (GDF‐9) in the granulosa cells of mature follicles. Methods: Follicular fluid (FF) was obtained from 13 patients with moderate to severe endometriosis and 11 without endometriosis, as a control group, and GDF‐9 protein levels in both were assayed by western blotting. mRNA expression by GDF‐9 and LH receptor (LHR) in granulosa cells obtained from all patients in the study were investigated by StepOne Real‐Time PCR. Results: Although GDF‐9 in FF from patients with endometriosis was no different from that of controls, GDF‐9 mRNA expression in granulosa cells of patients with endometriosis was statistically significantly lower than for the control group. The number of oocytes and high‐quality embryos was positively correlated with GDF‐9 mRNA expression in controls but not in patients with endometriosis Moreover, a negative correlation was identified between GDF‐9 mRNA expression and serum estrogen and progesterone levels in the control group, whereas no correlation was observed for the endometriosis group. Conclusions: Moderate to severe endometriosis can significantly reduce GDF‐9 mRNA expression in the granulosa cells of patients with the disease compared with those without, thus causing poor oocyte maturation and lower embryo quality.